Nano composition with acne removing effect as well as preparation method and application of nano composition

By using amphiphilic polymer encapsulation technology, a high-efficiency anti-acne nanocomposition is prepared, which solves the problem of existing products' poor effect on unbroken acne and the poor water solubility of high-efficiency anti-acne agents, achieving better acne removal. Acne effectiveness and safety.

CN119302871APending Publication Date: 2025-01-14HUANGPU INST OF MATERIALS
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411261475.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing acne removal products are not effective for unbreakable acne, and the water-soluble high-efficiency acne removal agents are poor, which limits their application in water essence. Common emulsifiers are irritating, further aggravating skin damage.

Method used

The amphiphilic polymer is used to encapsulate the anti-acne agent, and through high-speed shearing treatment of polyol solution and water, combined with high-pressure homogenization technology, a nanocomposition with high encapsulation rate and good transdermal permeability is prepared.

Benefits of technology

It achieves effective acne removal for unbroken skin acne, improves the water solubility and safety of the product, reduces skin irritation, and has better acne removal effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a nano composition with a deep acne removal effect and a preparation method and application thereof.The preparation method includes the steps that a straight-chain alkane structural unit (containing six or more carbon atoms) is adopted as an initiator to initiate a hydrophilic polymeric monomer to be subjected to a polymerization reaction, an amphiphilic polymer is prepared, acne removal active ingredients are entrapped, and the nano composition with the deep acne removal effect is obtained; the obtained nano composition has high encapsulation efficiency, and the encapsulation efficiency can reach 53.8% or above, and even can reach 80% or above. Meanwhile, the acne-removing nano composition has good percutaneous permeability and antibacterial effect and can be used for preparing acne-removing products, and the acne-removing effect of the acne-removing nano composition is remarkably superior to that of other acne-removing products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of nano-carriers, and in particular relates to a nano-composition with deep acne-removing effect and a preparation method and application thereof. Background Art

[0002] Acne is a chronic inflammatory skin disease of the pilosebaceous gland unit. It can occur at any age, but is most common in adolescents and is the second most common skin disease. It usually takes 2-6 weeks for acne to form, and the pores begin to become clogged. The formation of acne is usually caused by the following factors: (1) Clogged skin pores. Hormones or external stimuli cause excessive proliferation and keratinization of hair follicle keratinocytes, resulting in clogged pores; (2) Excessive secretion of skin oil. Androgens are converted into DHT under the catalysis of 5α-reductase, which highly binds to androgen receptors, stimulating the sebaceous gland cells to become overactive, producing excessive skin oil and accumulating it. (3) Abnormal colonization of Propionibacterium acnes. Propionibacterium acnes (P. acnes) abnormally colonizes and proliferates in clogged pores. (4) Inflammation. Propionibacterium acnes secretes a variety of enzymes to stimulate and produce inflammatory responses. Propionibacterium acnes stimulates monocytes to produce inflammatory factors and stimulates the body to produce defensins. It stimulates hair follicle keratinocytes to produce inflammatory factors. (5) Barrier damage. Propionibacterium acnes stimulates hair follicle keratinocytes to produce matrix metalloproteinases to decompose the extracellular matrix.

[0003] At present, there are mainly the following types of acne treatments: (1) using acidic substances (salicylic acid, azelaic acid, etc.) to dissolve in exfoliated keratin and keratinized hair follicles; (2) using glucocorticoids, vitamin A acid and other substances to resist acne inflammation; (3) using anti-androgen oil control treatments such as ethinyl estradiol, drospirenone, and spironolactone; (4) using antibiotics (tetracyclines or macrolides such as erythromycin, roxithromycin, and azithromycin); (5) physical and chemical treatments, such as photodynamic therapy, red and blue light, laser and photon therapy, and chemical peeling. However, the above common "acne removal" methods usually have side effects, such as frequent sensitive skin after acid peeling, damaged skin barrier, changes in epidermal microecology, bacterial resistance, and pigmentation. Therefore, a gentler, safer, and more effective "acne removal" is still a hot topic.

[0004] For harmful microorganisms in the hair follicle sebaceous gland unit, selecting highly effective acne-removing and anti-inflammatory agents to inhibit the colonization and proliferation of harmful microorganisms is an effective way to remove acne. For example, highly effective and novel acne-removing and anti-inflammatory agents such as quaternary ammonium salt-73, peptide sulfur, totarol, etc. have significant antibacterial effects on Propionibacterium acnes in the hair follicle sebaceous gland unit, and therefore have good acne-removing effects. However, the above-mentioned highly effective acne-removing agents are applied to acne-removing essences, and it is generally reported that they only have acne-removing effects on broken skin pimples, while for acne in the early stage of formation, the pimples that have not broken skin fail to play their due effects, thereby limiting their further application. In addition, the water solubility of the above-mentioned high-efficiency acne removers is very poor, and they are greatly limited in aqueous essences. In the prior art, a large amount of emulsifiers (such as polyglycerol emulsifiers, polysorbate emulsifiers, hydrogenated castor oil emulsifiers, etc.) are often used to pre-emulsify the high-efficiency acne removers and then add them to the formula. However, a high content of emulsifiers has a certain irritation and will further aggravate the damage of acne skin. Summary of the invention

[0005] In order to overcome the limitations of the above-mentioned prior art in the application of efficient and novel acne-removing and anti-inflammatory agents in acne-removing products, the primary purpose of the present invention is to provide a method for preparing a nano-composition with all-round deep acne-removing effects.

[0006] Another object of the present invention is to provide a nanocomposition prepared by the above method having all-round deep acne removal effect.

[0007] The present invention also provides the use of the nanocomposition prepared by the above method and having all-round deep acne removal effect.

[0008] The technical solution of the present invention is as follows:

[0009] A method for preparing a nanocomposition with deep acne-removing effect, wherein the nanocomposition is prepared by encapsulating an acne-removing agent in an amphiphilic polymer, comprising the following steps:

[0010] (1) adding an amphiphilic polymer, a stabilizer, and an anti-acne agent to a polyol, heating and stirring to obtain an alcohol phase solution, wherein the mass percentages of the amphiphilic polymer, the stabilizer, and the anti-acne agent in the nanocomposite are 0.5%-5%, 0.01%-0.3%, and 0.1%-1.5%, respectively, and the stabilizer is a triterpenoid compound;

[0011] (2) adding the alcohol phase solution dropwise into water and subjecting it to high-speed shear treatment to obtain a mixed solution;

[0012] (3) removing the polyol from the mixed solution and then homogenizing it under high pressure to obtain a nanocomposite;

[0013] The amphiphilic polymer is prepared by using a straight-chain diol with a carbon number of 6 or above as an initiator and connecting hydrophilic blocks to both ends of the initiator molecule.

[0014] Preferably, the stabilizer is at least one of glycyrrhetinic acid, licorice chalcone, and stearyl glycyrrhetinate; the initiator has 6-21 carbon atoms; and the hydrophilic block of the amphiphilic polymer is poly-2-methacryloyloxyethyl phosphorylcholine (PMPC).

[0015] Preferably, the initiator is one or more of 1,6-hexanediol (HEXA), 1,7-heptanediol (HEPT), 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,14-tridecanediol, 1,14-tetradecanediol (TEDE), and 1,21-heneicosanediol (HENE).

[0016] Preferably, the mass percentages of the amphiphilic polymer, stabilizer and anti-acne agent in the nanocomposition are 2±1%, 0.1±0.05% and 0.4±0.2%, respectively.

[0017] Preferably, the hydrophilic block (PMPC) of the amphiphilic polymer is obtained from the polymer monomer 2-methacryloyloxyethyl phosphorylcholine (MPC) by atom transfer radical polymerization (ATRP), and has a degree of polymerization of 15-30 and a molecular weight of 4000-9000; the acne remover includes at least one of quaternary ammonium salt-73, colloidal sulfur, and totarol; the mass percentage of the polyol in the nanocomposition is 5.0-20%.

[0018] Preferably, the heating temperature in step (1) is 40-80° C.; the stirring speed is 100-600 rpm; and the stirring time is 0.5-6 h.

[0019] Preferably, the polyol is a polyol with 5 or more carbon atoms in the molecular chain, including at least one of 1,2-hexanediol, dipropylene glycol, ethoxydiglycol, 1,8-octanediol, and octyldodecanol.

[0020] Preferably, the dropping speed in step (2) is 0.5-5 mL / min; the high-speed shear treatment is performed by using a high-speed shear homogenizer to perform high-speed shear treatment on the mixed solution during the process of dropping the oil phase into the water phase, the rotation speed is 5000-10000 rpm, and the shear dispersion time is until the dropping is completed; after the dropping is completed, stirring is performed at 100-600 rpm for 0.5-6 h.

[0021] Preferably, in step (3), the polyol in the mixed solution is removed by dialysis treatment, the molecular weight cutoff of the dialysis bag is greater than the molecular weight of the polyol, the pore size is much smaller than the particle size of the nanocomposite, and is 500-2000Da, and the dialysis treatment time is 6-24h.

[0022] Preferably, the high-pressure homogenization in step (4) is carried out by membrane extrusion, the membrane is a polycarbonate membrane, the pressure is 1.2-6.8 MPa, and the time is 10-30 min.

[0023] Preferably, the method for preparing the amphiphilic polymer comprises the following steps:

[0024] (1) mixing the initiator and the bromination reagent uniformly, reacting at 0-30° C. for 4-10 hours under the protection of an inert gas, to obtain a brominated initiator;

[0025] (2) Adding a polymerizable monomer, 2-methacryloyloxyethylphosphorylcholine (MPC), a brominated initiator, a catalyst and a catalyst ligand to an organic solvent, mixing the mixture evenly, and reacting the mixture under inert gas protection at 60-100° C. and 3-5 bar pressure for 6-10 hours to prepare an amphiphilic polymer.

[0026] Preferably, the catalyst comprises one or more of CuBr, CuCl, and CuI; and the catalyst ligand is an amine or ammonium catalyst ligand.

[0027] Preferably, the molar ratio of the initiator to the bromination reagent is 1:4.0-12.0; the molar ratio of the brominated initiator to the polymerization monomer, catalyst, and catalyst ligand is 1:(30-60):(0.1-0.5):(1-5).

[0028] Preferably, the catalyst ligand includes one or more of N,N-diisopropylethylamine, ethanolamine, N,N,N',N',N"-pentamethyldiethylenetriamine, and tetrabutylammonium bromide.

[0029] Preferably, the bromination reagent includes one or more of 2-bromoisobutyryl bromide, tert-butyl 2-bromoisobutyrate, and ethyl 2-bromoisovalerate.

[0030] The inert gas is an inert gas commonly used in the art, including one or more of nitrogen, argon, and helium, among which argon is preferred.

[0031] Preferably, the organic solvent includes at least one of N,N-dimethylformamide, N,N-dimethylacetamide and dimethyl sulfoxide.

[0032] Preferably, after the reaction of the amphiphilic polymer is completed, a purification step is further included: the amphiphilic polymer is slowly added to an organic precipitant, subjected to precipitation purification treatment, filtered, the filter cake is rinsed with the organic precipitant for multiple times, and dried at 25-40°C for 10-20h to obtain a refined amphiphilic polymer; the organic precipitant includes at least one of methanol, ethanol, n-hexane, and petroleum ether; and the temperature of the precipitation purification treatment is -10-10°C.

[0033] The nanocomposition with deep acne removal effect prepared by the above method is used in the preparation of acne removal products, which include acne removal creams and acne removal skin care products, such as acne removal cleansers, acne removal creams, acne removal masks, etc.

[0034] Preferably, the stirring method is mechanical stirring or magnetic stirring.

[0035] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0036] (1) The present invention uses a straight-chain alkane structural unit (containing more than 6 carbon atoms) as an initiator to initiate a polymerization reaction of a hydrophilic polymer monomer to prepare an amphiphilic polymer, and encapsulates the highly effective acne-removing active ingredient. The obtained nanocomposite has a high encapsulation rate, which can reach more than 53.8%, or even more than 80%. In particular, the present invention unexpectedly found that the polymer prepared by using quaternary ammonium salt-73 as the highly effective acne-removing active ingredient and selecting 1,7-heptanediol (a straight-chain alkane structure containing 7 carbon atoms) which is similar to the active ingredient has an excellent encapsulation effect on the highly effective acne-removing active ingredient quaternary ammonium salt-73, and the encapsulation rate of the final product can be as high as 98.9%.

[0037] (2) Compared with the highly efficient acne-removing active ingredients that have not been encapsulated, the acne-removing nanocomposition of the present application has better transdermal permeability and antibacterial effect. In addition, compared with the liposome encapsulation and surfactant solubilization methods in the prior art, the product of the present invention has better transdermal permeability, with a permeability of more than 50%, or even more than 60%. In particular, the present application uses 1,7-heptanediol (a straight-chain alkane structure containing 7 carbon atoms) with a similar molecular structure to the highly efficient acne-removing active ingredient as an initiator, and the prepared polymer encapsulates the highly efficient acne-removing active ingredient quaternary ammonium salt-73. The final product has a transdermal permeability of up to 93.5%, better antibacterial effect, lower irritation to human skin, and better acne removal effect. Therefore, the acne-removing nanocomposition of the present application has the advantages of being gentler, safer, and more effective in "removing acne". BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 The antibacterial test results of the samples of Example 1, Comparative Example 6 and Comparative Example 7 are shown.

[0039] Figure 2 This is a picture of the acne removal effect after the subject used the essence of Example 1. DETAILED DESCRIPTION

[0040] The present invention is further described in detail below in conjunction with the examples, but the embodiments of the present invention are not limited thereto. If the specific conditions are not indicated in the examples, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not indicated for the reagents or instruments used, they are all conventional products that can be purchased commercially. The reagents used in the examples can be purchased conventionally from the market unless otherwise specified.

[0041] In the embodiments of the present invention, the quaternary ammonium salt-73, gelatin peptide sulfur and totarol used can be directly purchased from Guangzhou Xiyuan Biotechnology Co., Ltd.

[0042] In the embodiments of the present invention, the glycyrrhetinic acid, licorice chalcone and stearyl glycyrrhetinate used can be directly purchased from Gansu Panzhi Pharmaceutical Co., Ltd.

[0043] Example 1

[0044] (1) Cationic polymer PMPC 20 -HEPT-PMPC 20 Preparation (taking the preparation of 1.0 mmol as an example): HEPT (0.132 g, 1.0 mmol) was added to tert-butyl 2-bromoisobutyrate (1.785 g, 8.0 mmol), with argon protection, and reacted at 25°C for 8 h to obtain Br-HEPT-Br. Br-HEPT-Br (0.362 g, 1.0 mmol), 2-methacryloyloxyethyl phosphorylcholine (11.811 g, 40.0 mmol), CuBr (0.045 g, 0.2 mmol), N,N-diisopropylethylamine (0.259 g, 2.0 mmol) were added to N,N-dimethylformamide (30 mL), mixed evenly, and argon was passed through. The mixture was reacted at 60° C. and 3.0 bar for 8 h. The reaction mixture was slowly added to 0° C. ethanol (300 mL), purified by precipitation, filtered, and the filter cake was washed 3 times with 0° C. ethanol (100 mL), and dried at 35° C. for 12 h to obtain the cationic polymer PMPC. 20 -HEPT-PMPC 20 (Number average molecular weight M n is 11943).

[0045] (2) The cationic polymer PMPC with a mass percentage of 2% was prepared 20 -HEPT-PMPC 20, 0.1% by mass of stearyl glycyrrhetinate and 0.4% by mass of quaternary ammonium salt-73 are added to 13% by mass of 1,2-hexanediol, heated to 60°C, stirred (at a speed of 400 rpm) for 3 hours to obtain an alcohol phase solution; the above-mentioned alcohol phase solution is uniformly added dropwise to 84.5% by mass of deionized water, and high-speed shear treatment (7000 rpm) is simultaneously started, the dropping speed is 2 mL / min, and after the dropwise addition is completed, stirring (at a speed of 400 rpm) is continued for 3 hours; the above-mentioned mixed solution is transferred to a dialysis bag (with a molecular weight cutoff of 1000 Da), and dialyzed in water of an equal volume to the mixed solution for 12 hours, and 1,2-hexanediol in the mixed solution is replaced by deionized water; after the dialysis is completed, the solution in the dialysis bag is taken, and it is squeezed through a filter membrane (pressure of 4.0 MPa) for 20 minutes to obtain a nano-composite with acne-removing effect.

[0046] Example 2

[0047] (1) Cationic polymer PMPC 20 -HEXA-PMPC 20 Preparation (taking the preparation of 1.0 mmol as an example): HEXA (0.118 g, 1.0 mmol) was added to tert-butyl 2-bromoisobutyrate (1.785 g, 8.0 mmol), and argon was passed through to react at 25°C for 8 h to obtain Br-HEXA-Br. Br-HEXA-Br (0.362 g, 1.0 mmol), 2-methacryloyloxyethyl phosphorylcholine (11.811 g, 40.0 mmol), CuBr (0.045 g, 0.2 mmol), N,N-diisopropylethylamine (0.259 g, 2.0 mmol) were added to N,N-dimethylformamide (30 mL), mixed evenly, and argon was passed through. The mixture was reacted at 60° C. and 3.0 bar for 8 h. The reaction mixture was slowly added to 0° C. ethanol (300 mL), purified by precipitation, filtered, and the filter cake was washed 3 times with 0° C. ethanol (100 mL), and dried at 35° C. for 12 h to obtain the cationic polymer PMPC. 20 -HEXA-PMPC 20 (The number average molecular weight Mn is 11928).

[0048] (2) Add 2.0% by mass of the polymer PMPC in Example 1 20 -HEPT-PMPC 20 Replaced with 2.0% polymer PMPC 20 -HEXA-PMPC 20 , and other conditions remain unchanged to obtain a nano-composite with acne-removing effect.

[0049] Example 3

[0050] (1) Cationic polymer PMPC 20 -TEDE-PMPC 20 Preparation (taking the preparation of 1.0 mmol as an example): TEDE (0.230 g, 1.0 mmol) was added to tert-butyl 2-bromoisobutyrate (1.785 g, 8.0 mmol), and argon was passed through to react at 25°C for 8 h to obtain Br-TEDE-Br. Br-TEDE-Br (0.474 g, 1.0 mmol), 2-methacryloyloxyethyl phosphorylcholine (11.811 g, 40.0 mmol), CuBr (0.045 g, 0.2 mmol), N,N-diisopropylethylamine (0.259 g, 2.0 mmol) were added to N,N-dimethylformamide (30 mL), mixed evenly, and argon was passed through. The mixture was reacted at 60° C. and 3.0 bar for 8 h. The reaction mixture was slowly added to 0° C. ethanol (300 mL), purified by precipitation, filtered, and the filter cake was washed 3 times with 0° C. ethanol (100 mL), and dried at 35° C. for 12 h to obtain the cationic polymer PMPC. 20 -TEDE-PMPC 20 (The number average molecular weight Mn is 12041).

[0051] (2) Add 2.0% by mass of the polymer PMPC in Example 1 20 -HEPT-PMPC 20 Replaced with 2.0% polymer PMPC 20 -TEDE-PMPC 20 , and other conditions remain unchanged to obtain a nano-composite with acne-removing effect.

[0052] Example 4

[0053] (1) Cationic polymer PMPC 20 -HENE-PMPC 20Preparation (taking the preparation of 1.0 mmol as an example): HENE (0.329 g, 1.0 mmol) was added to tert-butyl 2-bromoisobutyrate (1.785 g, 8.0 mmol), and argon was passed through to react at 25°C for 8 h to obtain Br-HENE-Br. Br-HENE-Br (0.572 g, 1.0 mmol), 2-methacryloyloxyethyl phosphorylcholine (11.811 g, 40.0 mmol), CuBr (0.045 g, 0.2 mmol), N,N-diisopropylethylamine (0.259 g, 2.0 mmol) were added to N,N-dimethylformamide (30 mL), mixed evenly, and argon was passed through. The mixture was reacted at 60° C. and 3.0 bar for 8 h. The reaction mixture was slowly added to 0° C. ethanol (300 mL), purified by precipitation, filtered, and the filter cake was washed 3 times with 0° C. ethanol (100 mL), and dried at 35° C. for 12 h to obtain the cationic polymer PMPC. 20 -HENE-PMPC 20 (The number average molecular weight Mn is 12139).

[0054] (2) Add 2.0% by mass of the polymer PMPC in Example 1 20 -HEPT-PMPC 20 Replaced with 2.0% polymer PMPC 20 -HENE-PMPC 20 , and other conditions remain unchanged to obtain a nano-composite with acne-removing effect.

[0055] (Examples 5-6 have different stabilizing ligands)

[0056] Example 5

[0057] The 0.1% by mass of stearyl glycyrrhetinate in Example 1 was replaced with 0.1% by mass of glycyrrhetinic acid, while other conditions remained unchanged, to obtain a nano-composition with all-round deep acne removal effect.

[0058] Example 6

[0059] The 0.1% by mass of stearyl glycyrrhetinate in Example 1 was replaced with 0.1% by mass of licorice chalcone, and the other conditions remained unchanged, to obtain a nano-composition with all-round deep acne removal effect.

[0060] (Examples 7-8 have different types of anti-acne active ingredients)

[0061] Example 7

[0062] The quaternary ammonium salt-73 with a mass percentage of 0.4% in Example 1 was replaced with totarol with a mass percentage of 0.4%, and other conditions remained unchanged, to obtain a nano-composition with all-round deep acne removal effect.

[0063] Example 8

[0064] The quaternary ammonium salt-73 with a mass percentage of 0.4% in Example 1 was replaced with colloidal sulfur with a mass percentage of 0.4%, and other conditions remained unchanged, to obtain a nano-composition with all-round deep acne removal effect.

[0065] (Examples 9-11 have different polymer addition amounts)

[0066] Example 9

[0067] The polymer PMPC with a mass percentage of 2.0% in Example 1 20 -HEPT-PMPC 20 Replaced with 0.5% by mass of polymer PMPC 20 -HEPT-PMPC 20 At the same time, 84.5% of deionized water by mass was replaced with 86% of deionized water by mass to make the total mass percentage 100%. The other conditions remained unchanged to obtain a nano-composition with acne-removing effect.

[0068] Example 10

[0069] The polymer PMPC with a mass percentage of 2.0% in Example 1 20 -HEPT-PMPC 20 Replaced with 4.0% polymer PMPC 20 -HEPT-PMPC 20 At the same time, the deionized water with a mass percentage of 84.5% is replaced with the deionized water with a mass percentage of 82.5% to make the total mass percentage 100%, and the other conditions remain unchanged to obtain a nano-composition with acne-removing effect.

[0070] Embodiment 11

[0071] The polymer PMPC with a mass percentage of 2.0% in Example 1 20 -HEPT-PMPC 20 Replaced with 5.0% polymer PMPC 20 -HEPT-PMPC 20 At the same time, the deionized water with a mass percentage of 84.5% is replaced with the deionized water with a mass percentage of 81.5% to make the total mass percentage 100%, and the other conditions remain unchanged to obtain a nano-composition with acne-removing effect.

[0072] (Examples 12-14 have different amounts of anti-acne active ingredients added)

[0073] Example 12

[0074] The quaternary ammonium salt-73 with a mass percentage of 0.4% in Example 1 was replaced with a quaternary ammonium salt-73 with a mass percentage of 0.1%, and the deionized water with a mass percentage of 84.5% was replaced with deionized water with a mass percentage of 84.8%, so that the total mass percentage was 100%. The other conditions remained unchanged, and a nanocomposition with acne-removing effect was obtained.

[0075] Example 13

[0076] The quaternary ammonium salt-73 with a mass percentage of 0.4% in Example 1 was replaced with a quaternary ammonium salt-73 with a mass percentage of 1.0%, and the deionized water with a mass percentage of 84.5% was replaced with deionized water with a mass percentage of 83.9%, so that the total mass percentage was 100%. The other conditions remained unchanged, and a nanocomposition with acne-removing effect was obtained.

[0077] Embodiment 14

[0078] The quaternary ammonium salt-73 with a mass percentage of 0.4% in Example 1 was replaced with a quaternary ammonium salt-73 with a mass percentage of 1.5%, and the deionized water with a mass percentage of 84.5% was replaced with a deionized water with a mass percentage of 83.4%, so that the total mass percentage was 100%. The other conditions remained unchanged, and a nanocomposition with acne-removing effect was obtained.

[0079] Comparative Example 1 (ethylene glycol as polymerization initiator)

[0080] (1) Cationic polymer PMPC 20 -EG-PMPC 20 Preparation (taking the preparation of 1.0 mmol as an example): Add ethylene glycol EG (0.062 g, 1.0 mmol) to tert-butyl 2-bromoisobutyrate (1.785 g, 8.0 mmol), pass argon protection, react at 25°C for 8 h to obtain Br-EG-Br. Br-EG-Br (0.306 g, 1.0 mmol), 2-methacryloyloxyethyl phosphorylcholine (11.811 g, 40.0 mmol), CuBr (0.045 g, 0.2 mmol), N,N-diisopropylethylamine (0.259 g, 2.0 mmol) were added to N,N-dimethylformamide (30 mL), mixed evenly, and argon was passed through. The mixture was reacted at 60° C. and 3.0 bar for 8 h. The reaction mixture was slowly added to 0° C. ethanol (300 mL), purified by precipitation, filtered, and the filter cake was washed 3 times with 0° C. ethanol (100 mL), and dried at 35° C. for 12 h to obtain the cationic polymer PMPC.20 -EG-PMPC 20 (Number average molecular weight Mn is 11873)

[0081] (2) Add 2.0% by mass of the polymer PMPC in Example 1 20 -HEPT-PMPC 20 Replaced with 2.0% polymer PMPC 20 -EG-PMPC 20 , and other conditions remain unchanged to obtain a nano-composite with acne-removing effect.

[0082] Comparative Example 2 (Molecular structure is nonlinear, 1,2-cycloheptanediol)

[0083] (1) Cationic polymer PMPC 20 -CyHEPT-PMPC 20 Preparation (taking the preparation of 1.0 mmol as an example): 1,2-cycloheptanediol (0.130 g, 1.0 mmol) was added to tert-butyl 2-bromoisobutyrate (1.785 g, 8.0 mmol), and argon was passed through to react at 25°C for 8 h to obtain Br-CyHEPT-Br. Br-CyHEPT-Br (0.374 g, 1.0 mmol), 2-methacryloyloxyethyl phosphorylcholine (11.811 g, 40.0 mmol), CuBr (0.045 g, 0.2 mmol), N,N-diisopropylethylamine (0.259 g, 2.0 mmol) were added to N,N-dimethylformamide (30 mL), mixed evenly, and argon was passed through. The mixture was reacted at 60° C. and 3.0 bar for 8 h. The reaction mixture was slowly added to 0° C. ethanol (300 mL), purified by precipitation, filtered, and the filter cake was washed 3 times with 0° C. ethanol (100 mL), and dried at 35° C. for 12 h to obtain the cationic polymer PMPC. 20 -CyHEPT-PMPC 20 (Number average molecular weight Mn is 11873)

[0084] (2) Add 2.0% by mass of the polymer PMPC in Example 1 20 -HEPT-PMPC 20 Replaced with 2.0% polymer PMPC 20 -CyHEPT-PMPC 20 , and other conditions remain unchanged to obtain a nano-composite with acne-removing effect.

[0085] Comparative Example 3 (without stabilizing ligand)

[0086] (1)PMPC 20-HEPT-PMPC 20 The preparation steps are the same as in Example 1.

[0087] (2) The cationic polymer PMPC with a mass percentage of 2% was prepared 20 -HEPT-PMPC 20 , 0.4% by mass of quaternary ammonium salt-73 is added to 13% by mass of 1,2-hexanediol, heated to 60°C, stirred (at a speed of 400 rpm) for 3 hours to obtain an alcohol phase solution; the above-mentioned alcohol phase solution is uniformly added dropwise to 84.6% by mass of deionized water, and high-speed shear treatment (7000 rpm) is simultaneously started, the dropping speed is 2 mL / min, and after the dropwise addition is completed, stirring (at a speed of 400 rpm) is continued for 3 hours; the above-mentioned mixed solution is transferred to a dialysis bag (with a molecular weight cutoff of 1000 Da), and dialyzed in water of an equal volume to the mixed solution for 12 hours, and 1,2-hexanediol in the mixed solution is replaced by deionized water; after the dialysis is completed, the solution in the dialysis bag is taken, and it is squeezed through a filter membrane (pressure of 4.0 MPa) for 20 minutes to obtain a nano-composite with acne-removing effect.

[0088] Comparative Example 4 (too much acne-removing active ingredient added)

[0089] The quaternary ammonium salt-73 with a mass percentage of 0.4% in Example 1 was replaced with a quaternary ammonium salt-73 with a mass percentage of 2.0%, and the deionized water with a mass percentage of 84.5% was replaced with a deionized water with a mass percentage of 82.9%, so that the total mass percentage was 100%. The other conditions remained unchanged, and a nanocomposition with acne-removing effect was obtained.

[0090] Comparative Example 5 (dialysis is not performed, i.e., the nanocomposition contains polyol)

[0091] (1)PMPC 20 -HEPT-PMPC 20 The preparation steps are the same as in Example 1.

[0092] (2) The cationic polymer PMPC with a mass percentage of 2% was prepared 20 -HEPT-PMPC 20, 0.1% by mass of stearyl glycyrrhetinate and 0.4% by mass of quaternary ammonium salt-73 are added to 13% by mass of 1,2-hexanediol, heated to 60°C, stirred (at a speed of 400 rpm) for 3 hours to obtain an alcohol phase solution; the above-mentioned alcohol phase solution is uniformly added dropwise to 84.5% by mass of deionized water, and high-speed shear treatment (7000 rpm) is simultaneously started, the dropping speed is 2 mL / min, and after the dropwise addition is completed, stirring is continued (at a speed of 400 rpm) for 3 hours; the above-mentioned mixed solution is subjected to membrane extrusion (pressure of 4.0 MPa) for 20 minutes to obtain a nano-composite with acne-removing effect.

[0093] Comparative Example 6 (Conventional Nanocarrier-Liposome)

[0094] 1% by mass of soybean lecithin, 0.1% by mass of cholesterol, and 0.4% by mass of quaternary ammonium salt-73 were dissolved in 30% by mass of ethanol, and stirred at 60°C (speed of rotation was 400rpm) for 3h. The ethanol solution was removed from the mixed solution by rotary evaporation (40°C, speed of rotation was 250rpm). After the ethanol was completely removed, 98.5% by mass of deionized water was added, and the mixture was dispersed by ultrasound (600w) for 30min, and finally subjected to membrane extrusion (pressure of 4.0MPa) for 20min to obtain liposomes encapsulating quaternary ammonium salt-73.

[0095] Comparative Example 7 (emulsifier emulsification method - Tween 80)

[0096] 0.4% by mass of quaternary ammonium salt-73 and 0.1% by mass of stearyl glycyrrhetinate are added to 3.0% by mass of 1,2-hexanediol, heated to 60° C., and stirred (at a speed of 400 rpm) until completely dissolved; then 10.0% by mass of Tween-80 is added, and stirred (at a speed of 400 rpm) for 30 minutes; then 86.5% by mass of deionized water is added, and stirred (at a speed of 400 rpm) at room temperature for 1 hour to obtain an anti-acne composition.

[0097] Test Example 1 Particle Size Characterization of Nanocomposite

[0098] The particle sizes of the samples of Examples 1-14 and Comparative Examples 1-7 were characterized by a Malvern Nano-ZS90 dynamic light scattering particle size analyzer. The test angle was 90° and the test temperature was 2°C. Three parallel experiments were performed for each group of experiments, and the arithmetic mean of the experimental results was taken.

[0099] Test Example 2 Characterization of Encapsulation Efficiency of Nanocomposites

[0100] The encapsulation efficiency of the acne-removing active ingredient was determined for the samples of Examples 1-14 and Comparative Examples 1-7. Take 200 μL of the acne-removing nanocomposition, centrifuge it through ultrafiltration (9000 rpm, 30 min), take 5 μL of the filtrate and measure the content of the acne-removing active ingredient in the filtrate through high performance liquid chromatography (HPLC, Shimadzu, Japan), and obtain the content of the acne-removing active ingredient not encapsulated in the acne-removing nanocomposition. Take the above acne-removing nanocomposition separately, add methanol solution, and ultrasonically demulsify it for 30 min according to the ratio of sample: methanol = 1:9 (v / v). After filtering with a 0.45 μm organic filter membrane, take 5 μL of the salt solution. The content of the anti-acne active ingredient was determined by a liquid chromatograph (HPLC, Shimadzu, Japan), and the content of the anti-acne active ingredient in the anti-acne nanocomposition was obtained. The encapsulation efficiency (EE) of the anti-acne active ingredient in the anti-acne nanocomposition was calculated according to formula (1). The analytical column used in the HPLC system was a non-polar C18 column, the flowability was acetonitrile and water (v:v = 8:2), the flow rate was 1.0 ml / min, the column temperature was 30 °C, and each group of experiments was conducted three times in parallel, and the experimental results were taken as the arithmetic mean.

[0101]

[0102] C1 represents the concentration of the unencapsulated anti-acne active substance in the sample, and C0 represents the concentration of the anti-acne active substance in the sample after ultrasonic demulsification with methanol solution.

[0103] Table 1 Particle size and encapsulation efficiency test results of samples of Examples 1-14 and Comparative Examples 1-7

[0104]

[0105]

[0106]

[0107] By comparing Examples 1-4, Comparative Example 1 and Comparative Example 2, it can be seen that the different types of linear initiators in the polymers result in different particle sizes and encapsulation rates of the acne-removing nanocompositions finally prepared. In Examples 1-4, the linear initiators are 1,7-heptanediol (HEPT), 1,6-hexanediol (HEXA), 1,14-tetradecanediol (TEDE), and 1,21-henedecanediol (HENE), respectively. The results show that as the carbon chain length (number of carbon atoms) in the linear initiator increases, the particle size of the sample gradually increases, but the encapsulation rate of the sample first increases and then decreases. When the linear initiator is 1,7-heptanediol (HEPT) (Example 1), the encapsulation rate of the sample is the highest, reaching 98.9%. When the carbon atoms of the linear initiator are less than 6, ethylene glycol EG (Comparative Example 1, carbon atoms are 2) is selected as the linear initiator, and the particle size of the acne-removing nanocomposite obtained is too large (518.7nm); the encapsulation rate is too low (18.7%). When the number of carbon atoms is kept the same (the number of carbon atoms is 7, which is consistent with Example 1), the non-linear 1,2-cycloheptanediol is selected as the initiator, and the particle size of the acne-removing nanocomposite obtained is too large (212.8nm); the encapsulation rate is too low (34.5). Therefore, in the present invention, the linear 1,7-heptanediol containing 7 carbon atoms is selected as the initiator, and the obtained polymer has the best encapsulation effect on the high-efficiency acne-removing active ingredient.

[0108] By comparing Example 1, Example 5, Example 6 and Comparative Example 3, it can be seen that the particle size and encapsulation efficiency of the final acne-removing nanocomposition are different due to different triterpenoid ligands. In Example 1, Example 5 and Example 6, the triterpenoid ligands are stearyl glycyrrhetinate, glycyrrhetinic acid and licorice chalcone, respectively. The results show that when the triterpenoid ligand is stearyl glycyrrhetinate, the final acne-removing nanocomposition (Example 1) has the smallest particle size of 67.1nm and the highest encapsulation efficiency of 98.9%. When no triterpenoid ligand is added (Comparative Example 3), the particle size of the final acne-removing nanocomposition is too large (197.5nm) and the encapsulation efficiency is too low (48.4%).

[0109] Comparison of Example 1, Example 7 and Example 8 shows that the particle size and encapsulation rate of the final anti-acne nanocomposition are different due to the different high-efficiency anti-acne active ingredients. In Example 1, Example 7 and Example 8, the high-efficiency anti-acne active ingredients are quaternary ammonium salt-73, totarol and colloidal sulfur respectively. The results show that compared with totarol (Example 7) and colloidal sulfur (Example 8), the polymer PMPC 20 -HEPT-PMPC 20 The encapsulation effect on quaternary ammonium salt-7 is the best, and the particle size of the acne-removing nanocomposite finally prepared is the smallest (67.1 nm) and the encapsulation rate is the highest (98.9%).

[0110] By comparing Example 1 and Examples 9-11, it can be seen that the particle size and encapsulation rate of the final anti-acne nanocomposition are different when the amount of polymer added is different. In Example 1 and Examples 9-11, the amount of polymer added is 2%, 0.5%, 4% and 5% respectively. The results show that as the amount of polymer added increases, the particle size of the final anti-acne nanocomposition first decreases and then increases, and the encapsulation first increases and then decreases. When the amount of polymer added is 2%, the particle size of the final anti-acne nanocomposition (Example 1) is the smallest and the encapsulation rate is the highest.

[0111] By comparing Example 1, Examples 12-14 and Comparative Example 4, it can be seen that the added amount of the efficient acne-removing active ingredient is different, and the particle size and encapsulation rate of the final acne-removing nanocomposition are different. In Example 1, Examples 12-14 and Comparative Example 4, the added amounts of the efficient acne-removing active ingredient are 0.4%, 0.1%, 1.0%, 1.5% and 2.0%, respectively. The results show that as the added amount of the efficient acne-removing active ingredient increases, the particle size of the final acne-removing nanocomposition gradually increases, while the encapsulation rate first increases and then decreases. When the added amount of the efficient acne-removing active ingredient is 2.0% (Comparative Example 4), its particle size is too large (327.9nm) and the encapsulation rate is too low (38.5%). Therefore, when the addition amount of the efficient acne-removing active ingredient selected in Example 1 of the present application is 0.4%, the encapsulation effect of the polymer on the active ingredient is optimal.

[0112] By comparing Example 1 with Comparative Example 5, it can be seen that in the preparation process of the anti-acne nanocomposition, dialysis operation is used to replace the polyol in the mixed solution with water, and the final anti-acne nanocomposition (Example 1) has a smaller particle size and a higher encapsulation rate.

[0113] By comparing Example 1, Example 6 and Example 7, it can be seen that compared with the method of using liposomes (Comparative Example 6) and surfactant solubilization (Comparative Example 7), the use of polymers to encapsulate the highly efficient acne-removing active ingredients gives an acne-removing nanocomposition (Example 1) with a smaller particle size and a higher encapsulation rate, that is, the acne-removing nanocomposition of Example 1 of the present invention has a better encapsulation effect on the highly efficient acne-removing active ingredients.

[0114] Test Example 3 Transdermal Absorption Test

[0115] The transdermal absorption (permeation promotion) test was used to evaluate the transdermal absorption (permeation promotion) ability of the acne-removing nanocompositions in Examples 1-14 and Comparative Examples 1-7, and the specific method is as follows:

[0116] The in vitro transdermal experiment used a vertical diffusion cell and nude mouse skin as a model (abdominal skin, subcutaneous fat layer and blood vessels removed). The receiving solution was PBS solution. The skin piece was fixed between the supply cell and the receiving cell, with the skin layer facing up, and balanced for 20 minutes. The permeation area was circular with a diameter of 1 cm. Each sample liquid (0.1 g) was added to the supply cell, and the receiving solution was taken after 1h, 4h, 8h and 24h. The receiving solution was ultrasonically demulsified with methanol solution, and the receiving solution: methanol = 1:9 (v / v), and then the content of the highly effective acne-removing active ingredient was determined by high-performance liquid chromatography (HPLC, Shimadzu, Japan), and the cumulative permeation per unit area was calculated based on this.

[0117] Each group of experiments was conducted three times in parallel, and the experimental results were taken as the arithmetic mean. The calculation formula for the unit cumulative permeation on the skin patch is shown in formula (2):

[0118]

[0119] Among them, Q n is the cumulative transmittance per unit area of ​​the sample at time t (μg / cm 2 ), A is the permeable area, C n is the concentration measured at time t, C i is the concentration measured before time t, V is the total volume of the receiving solution, and V0 is the sampling volume.

[0120] After the 24-hour in vitro transdermal experiment, the mouse skin with effective permeation area was removed and rinsed with physiological saline to avoid residual acne-removing active ingredients on the surface of the mouse skin that would affect the results. Then the skin was dried and cut into pieces of about 1 mm × 1 mm in size. It was placed in a small bottle, and methanol was added (the liquid level exceeded the skin fragments, but not more than 5 mL). Ultrasonication was performed for 5 minutes, and the supernatant was taken and filtered with a 0.22 μm filter membrane. The content of the highly effective acne-removing active ingredients was determined by high-performance liquid chromatography (HPLC, Shimadzu, Japan), and the retention amount of the highly effective acne-removing active ingredients per unit area was calculated based on this.

[0121] The permeation amount, retention amount and permeability per unit area of ​​the active ingredients in the samples of Examples 1-14, Comparative Examples 1-7 and quaternary ammonium salt-73 butanediol solution (mass percentage of 0.4%) are shown in Table 2.

[0122] Table 2

[0123]

[0124]

[0125] By comparing Examples 1-4, Comparative Example 1 and Comparative Example 2, it can be seen that the different types of linear initiators in the polymers result in different transdermal performance of the acne-removing nanocompositions finally prepared. The results show that as the carbon chain length (number of carbon atoms) in the linear initiator increases, the transdermal performance of the acne-removing nanocomposition samples finally prepared increases first and then decreases. When the linear initiator is 1,7-heptanediol (HEPT) (Example 1), the cumulative permeation per unit area of ​​the highly effective acne-removing active ingredient in the final product at 1h, 4h, 8h and 24h is 6.68μg / cm 2 41.50μg / cm 2 , 70.22μg / cm 2 , 212.82μg / cm 2 ; The active substance retention per unit area for 24 hours is 143.27μg / cm 2 The permeability of active substance per unit area in 24h is 93.5%, which is higher than that of samples in Examples 1-4, Comparative Example 1 and Comparative Example 2, indicating that the transdermal performance of Example 1 is the best.

[0126] By comparing Example 1, Example 5, Example 6 and Comparative Example 3, it can be seen that the transdermal performance of the final anti-acne nanocomposition is different when the triterpenoid ligand is different. In Example 1 of the present application, when the triterpenoid ligand is selected as stearyl glycyrrhetinate, the cumulative permeation amount per unit area, retention amount and permeability of the high-efficiency anti-acne active substance in the final product are the highest, indicating that Example 1 has the best transdermal performance.

[0127] By comparing Example 1, Example 7 and Example 8, it can be seen that the different high-efficiency acne-removing active ingredients result in different transdermal properties of the acne-removing nanocompositions. Compared with totarol (Example 7) and colloidal sulfur (Example 8), the polymer PMPC used in Example 1 of the present application 20 -HEPT-PMPC 20 When quaternary ammonium salt-7 is encapsulated, the cumulative permeation amount per unit area, retention amount and permeability of the high-efficiency anti-acne active ingredient in the final product are the highest, indicating that the transdermal performance of Example 1 is the best.

[0128] By comparing Example 1 and Examples 9-11, it can be seen that the transdermal performance of the final anti-acne nanocomposition is different when the amount of polymer added is different. As the amount of polymer added increases, the transdermal performance of the final anti-acne nanocomposition first increases and then decreases. When the amount of polymer added is 2% (Example 1), the cumulative permeation amount per unit area, retention amount and permeability of the high-efficiency anti-acne active substance in the final product are the highest, indicating that the transdermal performance of Example 1 is the best.

[0129] By comparing Example 1, Examples 12-14 and Comparative Example 4, it can be seen that the transdermal performance of the final anti-acne nanocomposition is different when the amount of the high-efficiency anti-acne active ingredient added is different. As the amount of the high-efficiency anti-acne active ingredient added increases, the transdermal performance of the final anti-acne nanocomposition first increases and then decreases. When the amount of the high-efficiency anti-acne active ingredient added is 0.4% (Example 1), the cumulative permeation amount per unit area, retention amount and permeability of the high-efficiency anti-acne active in the final product are the highest, indicating that Example 1 has the best transdermal performance.

[0130] By comparing Example 1 and Comparative Example 5, it can be seen that in Example 1 of the present application, during the preparation of the anti-acne nanocomposition, dialysis operation is used to replace the polyol in the mixed solution with water, and the cumulative permeation amount per unit area, retention amount and permeability of the high-efficiency anti-acne active substance in the final product are the highest, indicating that Example 1 has the best transdermal performance.

[0131] Comparison of Example 1, Example 6, Example 7 and quaternary ammonium salt-73 butanediol solution (mass percentage of 0.4%) shows that compared with liposomes (Comparative Example 6), surfactant solubilization (Comparative Example 7) and quaternary ammonium salt-73 butanediol solution (mass percentage of 0.4%) without encapsulation treatment, the polymer PMPC in Example 1 20 -HEPT-PMPC 20 When quaternary ammonium salt-7 is encapsulated, the cumulative permeation amount per unit area, retention amount and permeability of the high-efficiency anti-acne active ingredient in the final product are the highest, indicating that the transdermal performance of Example 1 is the best.

[0132] Test Example 4 Antibacterial Test

[0133] Propionibacterium acnes is the main harmful bacteria in the formation process of acne. Therefore, this test example uses Propionibacterium acnes as an antibacterial experimental model to test the antibacterial effect of the sample on Propionibacterium acnes.

[0134] Test objects: Example 1, Comparative Examples 1-7.

[0135] Test conditions: The initial concentration of Propionibacterium acnes was 3x10 7 CFU / mL, the solution volume was 20mL, the sample dosage was 0.5g / L, and the antibacterial effect of the sample was tested after culturing in a constant temperature anaerobic environment at 37℃ for 24h.

[0136] The antibacterial rates after using each sample were compared to evaluate the antibacterial effects of the tested samples.

[0137] Table 3 Antibacterial test results of samples of Example 1 and Comparative Examples 1-7

[0138] sample Antibacterial rate (%) Example 1 >90 Comparative Example 1 41 Comparative Example 2 62 Comparative Example 3 58 Comparative Example 4 54 Comparative Example 5 55 Comparative Example 6 54 Comparative Example 7 60

[0139] The antibacterial test results of the samples of Example 1 and Comparative Examples 1-7 are shown in Table 3. The antibacterial rate of the acne-removing nanocomposition of Example 1 is higher than 90%. The antibacterial rates of the samples of Comparative Examples 1-7 are 41%, 62%, 58%, 54%, 55%, 54% and 60%, respectively, which are all lower than the antibacterial rate of the acne-removing nanocomposition of Example 1, indicating that the method in Example 1 has a better encapsulation capacity for the acne-removing active ingredient, and the obtained acne-removing nanocomposition has the best antibacterial effect.

[0140] Test Example 5 Skin irritation test

[0141] Test objects: Example 1, Comparative Examples 1-7 and quaternary ammonium salt-73 butanediol solution (mass percentage is 0.4%).

[0142] The specific method of the multiple skin irritation test in the present invention is tested with reference to the standards in the "Technical Specifications for Safety of Cosmetics" (2015 edition), and the specific method is as follows:

[0143] Thirty-six white rabbits meeting the test conditions were prepared (four white rabbits were used for each sample), and the hair on both sides of the rabbits' back spines were trimmed before the test (the hair removal area was 3 cm×3 cm each).

[0144] Take 1.0g of the sample and apply it on one side of the skin (the application area is 2.5cm×2.5cm), and leave the other side untreated as a control. Apply once a day for 14 consecutive days. From the second day onwards, trim the hair before each application. Use pure water to remove the residual test substance. Observe the results after 1 hour.

[0145] Score according to Table 4 of the Skin Irritation / Corrosion Test of the "Technical Specification for Safety of Cosmetics" (2015 Edition), and treat the control area and the test area in the same way.

[0146] Table 4 Skin irritation reaction scores

[0147]

[0148] Result evaluation: Calculate the average score of each rabbit per day according to the following formula (3), and determine the skin irritation intensity of the rabbit according to the skin irritation / corrosion test table of the "Safety Technical Specifications for Cosmetics" (2015 edition). During the test, observe whether the skin has other symptoms other than skin irritation.

[0149]

[0150] Table 5 Skin irritation intensity classification

[0151] Integral mean strength 0-<0.5 Non-irritating 0.5-<2.0 Mild irritation 2.0-<6.0 Moderate irritation 6.0–8.0 Strong irritation

[0152] Data analysis: Compare the average daily score of each rabbit after using the sample, and grade the skin irritation intensity according to Table 5 to evaluate whether the sample is irritating.

[0153] Table 6 Skin irritation test results of Example 1, Comparative Examples 1-7 and Quaternary ammonium salt-73 butanediol solution (mass percentage 0.4%)

[0154]

[0155]

[0156] The skin irritation test results of Example 1, Comparative Examples 1-7 and quaternary ammonium salt-73 butanediol solution (mass percentage 0.4%) are shown in Table 6. In the skin irritation test, the average score of the acne-removing nanocomposition of Example 1 was 0.14, which was non-irritating. In the skin irritation test, the average scores of the acne-removing nanocompositions of Comparative Examples 1 and Comparative Examples 2 were 1.43 and 0.93, respectively, both of which were mildly irritating, indicating that the use of the polymer PMPC 20 -HEPT-PMPC 20 The high-efficiency acne-removing active molecules are encapsulated, and the skin irritation of the final sample is lower. In the skin irritation test, the average score of the acne-removing nanocomposition of Comparative Example 3 is 1.21, which is mild irritation, indicating that the addition of the triterpenoid ligand stearyl glycyrrhetinate makes the skin irritation of the final sample lower. In the skin irritation test, the average score of the acne-removing nanocomposition of Comparative Example 4 is 2.36, which is moderate irritation, indicating that the addition of the high-efficiency acne-removing active ingredient is too high (2.0% in Comparative Example 4), which will cause the final sample to be more irritating. In the skin irritation test, the average score of the acne-removing nanocomposition of Comparative Example 5 is 1.93, which is mild irritation, indicating that in the preparation process of the acne-removing nanocomposition, a dialysis operation is used to replace the polyol in the mixed solution with water, and the skin irritation of the final sample is lower. In the skin irritation test, the average scores of the acne-removing nanocompositions of Comparative Examples 6 and 7 were 2.50 and 2.93, respectively, both of which were moderately irritating, indicating that compared with liposomes (Comparative Example 6) and surfactant solubilization (Comparative Example 7), the acne-removing nanocomposition in Example 1 of the present invention is less irritating to the skin. In addition, the average skin irritation score of the quaternary ammonium salt-73 butanediol solution (mass percentage of 0.4%) sample was 2.21, which was moderately irritating. Therefore, the use of polymer nano-encapsulation technology can effectively reduce the irritation of the high-efficiency acne-removing functional molecules to the skin. In particular, the acne-removing nanocomposition of Example 1 of the present application has the best effect in reducing skin irritation.

[0157] Test Example 6: Acne Removal Effect

[0158] Test object: As shown in Table 7, Example 1, Comparative Examples 1-7 and quaternary ammonium salt-73 butanediol solution (mass percentage is 0.4%) are prepared into an anti-acne essence with a content of 10% as the test sample for this test.

[0159] Table 7 Anti-acne Essence Formula

[0160]

[0161]

[0162] Testing method: A single-blind, self-controlled before and after test was used. 45 volunteers (5 for each sample on average) aged 21-26 were selected. The volunteers were required to be type I (mild) acne patients, of which the proportion of acne without skin breakage must be greater than 80%. No cosmetics or pharmaceutical products can be used 3 days before the test. During the test, after cleansing the skin with water, take an appropriate amount of sample and apply it evenly on the test area (face, acne). Use the sample twice a day (once in the morning and once in the evening), and the test cycle is 14 days. Use the Antera 3D facial camera analyzer to compare the acne coverage area before and after using the sample. For details, see Figure 2 .

[0163] Table 8 Change rate of acne coverage area after subjects used samples (%)

[0164]

[0165]

[0166] As can be seen from Table 8, after using the test essence samples for 14 days, the change rates of acne coverage area on the faces of the subjects were -81.59% (essence of Example 1), -18.68% (essence of Comparative Example 1), -20.36% (essence of Comparative Example 2), 17.85% (essence of Comparative Example 3), 11.47% (essence of Comparative Example 4), 15.56% (essence of Comparative Example 5), -8.89% (essence of Comparative Example 6), -9.15% (essence of Comparative Example 7), and -10.11% (quaternary ammonium salt-73 essence (unencapsulated)). The results show that the acne removal effect of the essence of Example 1 is the most obvious, which is better than the essences of Comparative Examples 1-7 and the quaternary ammonium salt-73 essence (unencapsulated), that is, the acne removal effect of Example 1 in the present application is the best.

[0167] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a nanocomposition with deep acne removal effect, characterized in that: The nanocomposition is prepared by encapsulating the anti-acne agent in an amphiphilic polymer, and comprises the following steps: (1) adding an amphiphilic polymer, a stabilizer, and an anti-acne agent to a polyol, heating and stirring to obtain an alcohol phase solution, wherein the mass percentages of the amphiphilic polymer, the stabilizer, and the anti-acne agent in the nanocomposite are 0.5%-5%, 0.01%-0.3%, and 0.1%-1.5%, respectively, and the stabilizer is a triterpenoid compound; (2) adding the alcohol phase solution dropwise into water and subjecting it to high-speed shear treatment to obtain a mixed solution; (3) removing the polyol from the mixed solution and then homogenizing it under high pressure to obtain a nanocomposite; The amphiphilic polymer is prepared by using a straight-chain diol with a carbon content of more than 6 as an initiator and connecting hydrophilic blocks to both ends of the initiator molecule.

2. The preparation method according to claim 1, characterized in that: The stabilizer is at least one of glycyrrhetinic acid, licorice chalcone and stearyl glycyrrhetinate; the number of carbon atoms of the initiator is 6-21; and the hydrophilic block of the amphiphilic polymer is poly-2-methacryloyloxyethyl phosphorylcholine.

3. The preparation method according to claim 2, characterized in that: The initiator is one or more of 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,14-tridecanediol, 1,14-tetradecanediol and 1,21-heneicosanediol.

4. The preparation method according to claim 3, characterized in that: The mass percentages of the amphiphilic polymer, stabilizer and acne-removing agent in the nanocomposite are 2±1%, 0.1±0.05% and 0.4±0.2% respectively.

5. The preparation method according to claim 4, characterized in that: The hydrophilic block of the amphiphilic polymer has a polymerization degree of 15-30 and a molecular weight of 4000-9000; the anti-acne agent comprises at least one of quaternary ammonium salt-73, colloidal sulfur and totarol; and the mass percentage of the polyol in the nanocomposite is 5.0-20%.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The heating temperature in step (1) is 40-80° C.; the stirring speed is 100-600 rpm; the stirring time is 0.5-6 h; the polyol is a polyol with 5 or more carbon atoms in the molecular chain, including at least one of 1,2-hexanediol, dipropylene glycol, ethoxydiglycol, 1,8-octanediol, and octyldodecanol; The dropping speed in step (2) is 0.5-5 mL / min; the high-speed shear treatment is to use a high-speed shear homogenizer to perform high-speed shear treatment on the mixed solution during the process of adding the oil phase to the water phase, the speed is 5000-10000 rpm, and the shear dispersion time is until the dropping is completed; after the dropping is completed, stirring at 100-600 rpm for 0.5-6h; Step (3) removing the polyol in the mixed solution by dialysis treatment, the molecular weight cut-off of the dialysis bag is greater than the molecular weight of the polyol, the pore size is much smaller than the particle size of the nanocomposite, and is 500-2000Da, and the dialysis treatment time is 6-24h; The high-pressure homogenization in step (4) is carried out by membrane extrusion, the membrane is a polycarbonate membrane, the pressure is 1.2-6.8 MPa, and the time is 10-30 min.

7. The preparation method according to claim 6, characterized in that: The preparation method of the amphiphilic polymer comprises the following steps: (1) mixing the initiator and the bromination reagent uniformly, reacting at 0-30° C. for 4-10 hours under the protection of an inert gas, to obtain a brominated initiator; (2) Adding a polymerizable monomer, 2-methacryloyloxyethyl phosphorylcholine, a brominated initiator, a catalyst and a catalyst ligand to an organic solvent, mixing the mixture evenly, and reacting the mixture under the protection of an inert gas at 60-100° C. and a pressure of 3-5 bar for 6-10 hours to prepare an amphiphilic polymer.

8. The preparation method according to claim 7, characterized in that: The catalyst includes one or more of CuBr, CuCl, and CuI; the catalyst ligand is an amine or ammonium catalyst ligand; The molar ratio of the initiator to the bromination reagent is 1:4.0-12.0; the molar ratio of the brominated initiator to the polymerization monomer, the catalyst, and the catalyst ligand is 1:(30-60):(0.1-0.5):(1-5); The catalyst ligand includes one or more of N,N-diisopropylethylamine, ethanolamine, N,N,N',N',N"-pentamethyldiethylenetriamine, and tetrabutylammonium bromide; The bromination reagent includes one or more of 2-bromoisobutyryl bromide, tert-butyl 2-bromoisobutyrate, and ethyl 2-bromoisovalerate; The inert gas includes one or more of nitrogen, argon and helium; The organic solvent includes at least one of N,N-dimethylformamide, N,N-dimethylacetamide and dimethyl sulfoxide; After the reaction of the amphiphilic polymer is completed, a purification step is further included: slowly adding the amphiphilic polymer to an organic precipitant, subjecting the amphiphilic polymer to a precipitation purification treatment, filtering, washing the filter cake with the organic precipitant for multiple times, and drying at 25-40° C. for 10-20 hours to obtain a refined amphiphilic polymer; the organic precipitant includes at least one of methanol, ethanol, n-hexane, and petroleum ether; and the temperature of the precipitation purification treatment is -10-10° C.

9. The nanocomposition with deep acne-removing effect obtained by the method according to any one of claims 1 to 8.

10. Use of the nanocomposition according to claim 9 in preparing an anti-acne product.

Citation Information

Cited By

  • Deep antioxidant EGCG (epigallocatechin gallate) nano composition as well as preparation method and application thereof

    CN120570800A

  • Acne-removing composition, liposome and preparation method and application thereof

    CN120899568A

  • A composition for treating acne, liposomes and a preparation method and application thereof

    CN120899568B